The Discovery of the Universal Mass-Energy Equivalence Relation in Materials Having a Bandgap - Chanana, Ravi Kumar (Transactions on Engineering and Computing Sciences, 2023)
This article describes how the discovery of the universal mass-energy equivalence relation came about and tabulates the possible high, medium and low voltage Metal-Oxide-Semiconductor-Field-Effect-Transistors (MOSFETs) from different semiconductors which could be n-channel or p-channel devices. Some points are to be considered for the tabulated MOSFETs which are enlisted. The universal mass-energy equivalence relation is given as dE/E = dm/m where, E is the energy and m is the mass. The article is published elsewhere but the author feels the need to widen publicity.